Birth Outcomes Associated With E-Cigarette and Non–E-Cigarette Tobacco Product Use During Pregnancy: An Examination of PATH Data Waves 1–5. Issue 3 (26th April 2022) - Cohn, Amy M; Elmasry, Hoda; Wild, Robert C; Johnson, Amanda L; Abudayyeh, Haneen; Kurti, Allison; Coleman-Cowger, Victoria H
Abstract: Objectives: To examine associations of prenatal e-cigarette use to pregnancy and birth outcomes. Methods: Currently pregnant women ( n = 1 037) from Waves 1 through 4 of the Population Assessment of Tobacco and Health Study who had pregnancy or live birth outcome data in a subsequent wave (Waves 2–5; 2013 to 2019). Weighted bivariate and multivariable models examined associations between past 30-day tobacco use assessed during pregnancy (any past 30-day e-cigarette use, any past 30-day non–e-cigarette tobacco use, or no past 30-day tobacco use) with adverse pregnancy (miscarriage, abortion, ectopic or tubal pregnancy, stillbirth) and birth outcomes (preterm birth, low birth weight, birth defect, placenta previa, placental abruption, pre-eclampsia) reported in the subsequent wave. Results: Approximately 1% of pregnant women reported past 30-day exclusive e-cigarette use and 3.2% used e-cigarettes and one other tobacco product. Compared to no tobacco use, past 30-day e-cigarette use (exclusive or use with another tobacco product) during pregnancy was not associated with increased odds of an adverse pregnancy or birth outcome in bivariate or multivariable models. Past 30-day non–e-cigarette tobacco use was associated with increased odds of an adverse pregnancy outcome in multivariable models, but not an adverse live birth outcome. Compared to past 30-day cigarette use, past 30-day e-cigarette use during pregnancy was not associated with lowered odds of a birth or pregnancy outcome. Conclusions: E-cigarette use during pregnancy is rare. Understanding the positive and negative impacts of pre–natal e-cigarette use on women's health may guide public health messaging campaigns. Implications: Results showed that past 30-day e-cigarette use during pregnancy was low, with cigarette smoking remaining the most prevalent form of tobacco use during pregnancy. Current e-cigarette use during pregnancy used either exclusively or with another tobacco product, was not associated with increased risk of an adverse pregnancy, or birth outcome. A small sample size of e-cigarette users and limited information on quantity and frequency of e-cigarette use before and during pregnancy may limit conclusions. Healthcare providers may use this information when discussing the harms and consequences associated with e-cigarette and tobacco use during pregnancy.